Whole Recombinant Saccharomyces cerevisiae Yeast Expressing Ras Mutations as Treatment for Patients With Solid Tumors Bearing Ras Mutations: Results From a Phase 1 Trial. Issue 3 (April 2018) - Cohn, Allen; Morse, Michael A.; O'Neil, Bert; Whiting, Samuel; Coeshott, Claire; Ferraro, John; Bellgrau, Donald; Apelian, David; Rodell, Timothy C.
Abstract : We are developing whole, heat-killed, recombinant Saccharomyces cerevisiae yeast, engineered to encode target proteins, which stimulate immune responses against malignant cells expressing those targets. This phase 1 trial, enrolling patients with advanced colorectal or pancreas cancer, was designed to evaluate safety, immunogenicity, response, and overall survival of ascending doses of the GI-4000 series of products, which express 3 different forms of mutated Ras proteins. The study enrolled 33 heavily pretreated subjects (14 with pancreas and 19 with colorectal cancer), whose tumors were genotyped before enrollment to identify the specific ras mutation and thereby to identify which GI-4000 product to administer. No dose limiting toxicities were observed and no subject discontinued treatment due to a GI-4000 related adverse event (AE). The majority of AEs and all fatal events were due to underlying disease progression and AE frequencies were not significantly different among dose groups. GI-4000 was immunogenic, as Ras mutation-specific immune responses were detected on treatment in ∼60% of subjects. No objective tumor responses were observed but based on imaging, clinical status and/or biochemical markers, stable disease was observed in 6 subjects (18%) on day 29, while 1 subject had stable disease at days 57 and 85 follow-up visits. The median overall survival was 3.3 months (95% confidence interval, 2.3–5.3 mo), and 5 subjects survived past the 48-week follow-up period. No significant dose-dependent trends for survival were observed. This first clinical trial in humans with GI-4000 demonstrated a favorable safety profile and immunogenicity in the majority of subjects.